Pengaruh Citra Merek, Inovasi Produk, dan Kualitas Produk Terhadap Keunggulan Bersaing Produk Wardah: Studi pada Masyarakat Kota Surabaya - Indy Melva Adinda Marsha; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of brand image, product innovation, and product quality on the competitive advantage of Wardah products by the people of Surabaya. This study is quantitative by taking 100 samples. Sampling using the non-probability sampling method and using a sampling technique in the form of purposive sampling with the criteria that respondents are domiciled in Surabaya, at least 17 years old, and have purchased or used Wardah brand lipstick products at least twice. The results of this study indicate that brand image, product innovation, and product quality simultaneously have a significant effect on the competitive advantage of Wardah products. brand image, product innovation, and product quality simultaneously have a significant effect on the competitive advantage of Wardah products. Brand image partially has a positive and significant effect on the competitive advantage of Wardah products. Product quality partially has a positive and significant effect on competitive advantage in Wardah products. Product innovation partially has a positive and significant effect on competitive advantage in Wardah products.